2021
DOI: 10.1002/pep2.24234
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of selected cathelicidins against infectious bronchitis virus

Abstract: Avian infectious bronchitis (IB) is a highly contagious disease caused by infectious bronchitis virus (IBV), a coronavirus of domestic fowl. IB is a major concern in the poultry industry, causing worldwide economic losses through decreased egg production and quality and by increasing the chicken's susceptibility for secondary bacterial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In IAV and RSV, LL-37 produced notable disruption of virions under electron microscopy 19 , 21 . For IBV, no virion disruption was observed by EM and the inhibitory effect was cell-type specific, suggesting an effect on other components of viral entry, such as the viral spike or host entry receptor 18 .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In IAV and RSV, LL-37 produced notable disruption of virions under electron microscopy 19 , 21 . For IBV, no virion disruption was observed by EM and the inhibitory effect was cell-type specific, suggesting an effect on other components of viral entry, such as the viral spike or host entry receptor 18 .…”
Section: Introductionmentioning
confidence: 93%
“…Early experiments with LL-37 and murine CRAMP cathelicidin peptides observed inhibition of multiple influenza A virus (IAV) strains both in cell culture and in murine infection experiments 17 . Later experiments with IAV, respiratory syncytia virus (RSV), and infectious bronchitis virus (IBV) indicated that LL-37 directly affects IAV, RSV, and IBV virions during cellular infection, as LL-37 added at the time of infection effectively inhibited either virus, but not when added to cells pre- or post-infection 18 20 . The lack of inhibition observed in pre-treated cells suggests that a minority of the inhibition is dependent on conditioning of host cells and that the majority of LL-37 is consumed within a few hours of addition.…”
Section: Introductionmentioning
confidence: 99%